Electroencephalographic characteristics of word finding during phonological and semantic verbal fluency tasks. Issue 3 (5th August 2020) - Mousavi, Najva; Nazari, Mohammad Ali; Babapour, Jalil; Jahan, Ali
Abstract: Aims: Verbal Fluency is sensitive to brain damage and is employed to assess language abilities like the size of vocabulary and the semantic‐lexical networks' integrity and executive functioning abilities particularly inhibition, working memory, and self‐monitoring. Various studies revealed oscillatory changes related to word retrieval during different tasks. However, there are not enough studies on electroencephalographic characteristics of word retrieval routes (phonological or semantic pathway) during free recall. The purpose of our study was to investigate electroencephalography power relationship with semantic and phonological word finding routes during verbal fluency. Methods: In this within‐subject study, the electroencephalography of 20 healthy participants was recorded during written category and letter fluency tasks and compared with the rest state. Absolute power of the signals in delta (1‐3.5 Hz), theta (4‐7.5 Hz), alpha (8‐12 Hz), and beta (12.5‐30 Hz) was calculated in three lobes (frontal, parietal, and temporal). Results: A repeated measures ANOVA showed significant interaction of condition × lobe × frequency × side ( P < .001). Post hoc test for each lobe showed significant changes in the absolute power of delta, theta and beta for frontal, delta and theta for parietal, and theta and beta for temporal lobes ( P ‐values < .05). Conclusion: Searching the words by phonological entries is associated with decreased beta and increased theta in left frontal lobe. These changes are not necessary for semantic word retrieval strategy. Abstract : Word retrieval either by phonological entries or semantic categories is accompanied by increased delta in frontal and parietal lobes. Decreased beta and increased theta bands in the left frontal lobe are associated with phonological word retrieval strategy while during semantic word finding, increased beta was observed in the left temporal lobe.